Distribution of Dinoflagellate Cysts in Surface Sediments From the Qingdao Coast, the Yellow Sea, China: The Potential Risk of Harmful Algal Blooms - Wang, Zhaohui; Zhang, Yuning; Lei, Mingdan; Ji, Shuanghui; Chen, Jiazhuo; Zheng, Hu; Tang, Yali; Hu, Ren (Frontiers in Marine Science, 2022)
Surface sediments were collected from three sea areas of the Qingdao coast, the Yellow Sea, China, namely, the inner Jiaozhou Bay, the Laoshan coast, and the Amphioxus Reserve area in November to December 2017. Dinoflagellate cysts were observed in the sediments, focusing on the distribution of toxic and harmful species. Contents of biogenic elements were analyzed to reveal their relationships to cysts. A total of 32 cyst taxa were identified, including 23 autotrophic and 9 heterotrophic taxa. Cyst concentrations ranged from 83.3 to 346.5 cysts/g D Wt with an average of 210.7 cysts/g D Wt. Generally, cysts of autotrophic dinoflagellates dominated in sediments from the Qingdao coast with proportions of 41.05%–90.25%. There were no dominant group in cyst assemblages; cysts of Protoperidiniaceae, Suessiales, and Calciodinelloideae showed similar contributions. Cyst assemblages were quite different in the inner Jiaozhou Bay reflected by the lower species richness, diversity, and cyst concentration. Results from the redundancy analysis (RDA) demonstrated the influence of biogenic elements on cyst assemblages, which explained well why the three sea areas with different degrees of human activities showed different dinocyst storages. Notably, 17 harmful algal bloom (HAB) dinoflagellate cysts were identified in this study, including cysts of those producing toxins that may damage human health and marine animals. Some of these cysts occurred widely and dominantly in this study, such as cysts of Gonyaulax spinifera, Azadinium trinitatum, Scrippsiella acuminata, and Biecheleria halophila, suggesting the potential risk of HABs in the Qingdao coastal area.